Right superior vena cava draining into the left atrium in a patient with sinus venosus defect. Issue 11 (21st August 2020) - Kanakis, Meletios; Martens, Thomas; Laskari, Cleo; Kousi, Theofili; Karafotia, Afroditi; Bobos, Dimitrios; Giannopoulos, Nicholas
Abstract: Right superior vena cava draining into the left atrium is an extremely rare anomaly of systemic venous return. It can be isolated or it can be associated with other congenital heart defects, thus clinical presentation may vary. A case of a 9‐year‐old asymptomatic patient with sinus venous defect and bilateral superior vena cava with the right‐sided draining into the left atrium is described.